Tensile performance of half-lap timber nailed joint strengthened using CFRP sheet / Nurain Rosdi … [et al.] - Rosdi, Nurain; Nik Yahya, Nik Norhafiza; Hassan, Rohana; Yasin, Mohd Hanafie; Abd Malek, Nor Jihan (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
The strength of timber structure will slightly reduce due to long service life or constantly sustained under excessive load. Some of the structural member may need to be replaced or rectified. This paper presents findings on the half-lap timber joint strengthened using carbon fibre reinforced polymer (CFRP). The selected timber species are from Malaysian tropical timber, namely Kelampayan (SG7) and Kempas (SG2). The size of each specimen was 41x100x600mm. Six (6) specimens were tested without and with CFRP sheet. Epoxy glue was used as the bonding agent. The behaviour of the specimen was studied through their load-deformation characteristic upon loading and compared to European Yield Model (EYM). Results show that the strengthened specimens performed better than without CFRP. For Kelampayan, the maximum loads for without and with CFRP were 6.33kN and 14.0 kN respectively. The tensile strength of the nailed connection with CFRP for Kelampayan has been increased by 121% compared to without CFRP. As for Kempas, the maximum loads for without and with CFRP are 15.8 kN and 25.0 kN respectively and the connection strength with CFRP has been increased by 58% compared to without CFRP. Both Kelampayan and Kempas failure mode have found failed in mode b for the with CFRP sheet while failure in mode c for the without CFRP sheet. Therefore, it is proven that the use of CFRP sheet has significantly increased the tensile strength of half-lap timber nailed joint for the two-selected species.